Materialities of Care 2018
DOI: 10.1002/9781119499749.ch3
|View full text |Cite
|
Sign up to set email alerts
|

Thinking with Care Infrastructures: People, Devices and the Home in Home Blood Pressure Monitoring

Abstract: The growing consumer market in health monitoring devices means that technologies that were once the preserve of the clinic are moving into spaces such as homes and workplaces. We consider how one such device, blood pressure monitors, comes to be integrated into everyday life. We pursue the concept of 'care infrastructure', drawing on recent scholarship in STS and medical sociology, to illuminate the work and range of people, things and spaces involved in selfmonitoring. Drawing on a UK study involving observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…The paper is based on a UK study involving interviews with people who self-identified as monitoring their blood pressure or BMI/weight. Our engagement with selfmonitoring stemmed from our broader interest in everyday health practices, the use of health technologies in domestic settings and the way these might redistribute health work between the home and the clinic (see Henwood and Marent, 2019;Weiner et al, 2017;Weiner and Will, 2018;Williams et al, 2020, forthcoming). Home blood pressure monitoring and BMI monitoring offer particularly interesting cases in the way they blur the boundary between the clinic and the home.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The paper is based on a UK study involving interviews with people who self-identified as monitoring their blood pressure or BMI/weight. Our engagement with selfmonitoring stemmed from our broader interest in everyday health practices, the use of health technologies in domestic settings and the way these might redistribute health work between the home and the clinic (see Henwood and Marent, 2019;Weiner et al, 2017;Weiner and Will, 2018;Williams et al, 2020, forthcoming). Home blood pressure monitoring and BMI monitoring offer particularly interesting cases in the way they blur the boundary between the clinic and the home.…”
Section: Methodsmentioning
confidence: 99%
“…Further, the idea of curation helps to link the work of making data with the emotional aspects of self-monitoring and the value of the data. In our analysis, we adopt this lens to develop a socio-materialist account (Henwood and Marent, 2019;Weiner and Will, 2018;Williams et al, 2020, forthcoming) of everyday data practices relating to selfmonitoring, exploring what records people keep, what materials are involved and whether and how records are shared. We suggest that this curatorial approach helps to clarify the relationship between selfmonitoring and the accrual and flow of data.…”
Section: Curation As Socio-materials Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Their focus is on the mundane elements that underpin medication practices, in decentering self-care from the locus of the individual. Weiner and Will (2018) apply the term to the context of home care monitoring, arguing that care infrastructures allow them 'to see the socio-technical relations behind care' (p. 272). Similarly, it helps illuminate spaces that are traditionally thought of as 'outside care', as 'designers, architects, and planners can orchestrate environments where care may take place with intended and unintended consequences' (Buse et al, 2018, p. 253).…”
Section: Concepts and Methodsmentioning
confidence: 99%
“…The challenges they face include but are not limited to: deciding whom and where to seek for medical service among numerous qualified medical doctors, puzzling out insurance and payment options, coordinating and communicating with multiple healthcare providers, selecting the optimal treatment plans, making sense of a vast amount of health data coming from different healthcare professionals, and negotiating socio-cultural boundaries between care settings, etc. These challenges force patients and caregivers to engage in ongoing "work" to (re)-configure, connect, communicate, construct, adapt and sustain different infrastructural arrangements between human and nonhuman entities (e.g., people, places, routines, physical and digital materials and artifacts) within and beyond the clinic [5,10,20]. Drawing on previous work on infrastructure" [17,18], we refer to this ongoing/dynamic work as "infrastructuring work" where multiple assembling entities have to work as a collective in order to make the often fragmented and broken healthcare services function for them.…”
Section: Introductionmentioning
confidence: 99%